Fine and Gross Motor Ability in Male and Female Adolescents with and without Developmental Coordination Disorder - Baynam, Grant; Piek, Jan (The Australian Psychological Society Ltd, 2003)
The present study examined fine and gross motor ability of male and female adolescents with and without Developmental Coordination Disorder (DCD). Sixty-four girls and 37 boys were compared across gender and level of motor ability measured with the McCarron Assessment of Neuromuscular Development (MAND).Although there was no significant difference in gross motor ability, adolescent males with DCD evidenced lower fine motor ability than females with DCD.The implications of these findings are discussed with reference to the necessity to assess specific sources of deficit,as well as gender differences in movement ability when tailoring intervention strategies, particularly within the academic setting.